Perceptions of stigma - Šadl, Zdenka (Teorija in praksa, 2014)
In this article the author investigates paid domestic work in Slovenia to obtain information on domestic workers' perceptions of their work. Cleaning up after other people is usually considered dirty work with a stigma attached to it. Given this, we draw on indepth interviews with paid domestic workers to examine how they deal with society's negative perceptions and potential individual strategies for coping with a stigmatised social identity. On the basis of previous research on paid domestic work it was assumed that employment relationships are arranged in such a way (because of the location, domesticity, informal management - all in a relatively traditional and constraining gendered order) that those employed as domestic workers do feel stigma, but we also assume (based on many studies on dirty work) that housecleaners share a relatively high level of self-respect and pride with other dirty workers. The results show that stigma intrudes into the social interactions between paid domestic workers and their employers, leading housecleaners to seek different strategies to cope with it. At the same time, respondents' descriptions of their work and work relations reveal positive aspects of the job and thus shed light on the complexity of cleaners' work and their employment relationships within the confines of the private domestic space.
Keywords: Gospodinjske delavke; Gospodinjsko delo; Housework; Slovenia; Slovenija; Stigma (Social psychology); Stigma (Socialna psihologija); stigmatizacija; Women household employees